2020
DOI: 10.1021/acs.chemrev.9b00427
|View full text |Cite
|
Sign up to set email alerts
|

Garnet-Type Solid-State Electrolytes: Materials, Interfaces, and Batteries

Abstract: Solid-state batteries with desirable advantages, including high-energy density, wide temperature tolerance, and fewer safety-concerns, have been considered as a promising energy storage technology to replace organic liquid electrolyte-dominated Li-ion batteries. Solid-state electrolytes (SSEs) as the most critical component in solid-state batteries largely lead the future battery development. Among different types of solid-state electrolytes, garnet-type Li7La3Zr2O12 (LLZO) solid-state electrolytes have partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
560
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 836 publications
(619 citation statements)
references
References 273 publications
8
560
1
1
Order By: Relevance
“…Tatsumisago et al [24] and Sakuda et al [25] published important reviews on sulfide electrolytes, while Thangadurai et al [26,27] reviewed garnet electrolytes. Furthermore, the fundamentals of ASSBs were reviewed by several authors [28][29][30][31][32][33][34][35]. The number of reviews on various aspects of electrolytes, cathodes, mechanical properties, and interface engineering has grown exponentially since 2018 .…”
Section: Introductionmentioning
confidence: 99%
“…Tatsumisago et al [24] and Sakuda et al [25] published important reviews on sulfide electrolytes, while Thangadurai et al [26,27] reviewed garnet electrolytes. Furthermore, the fundamentals of ASSBs were reviewed by several authors [28][29][30][31][32][33][34][35]. The number of reviews on various aspects of electrolytes, cathodes, mechanical properties, and interface engineering has grown exponentially since 2018 .…”
Section: Introductionmentioning
confidence: 99%
“…To solve the challenge of interfacial resistance in SEs, Wang et al suggested a method of coating nanoscale and lithiophilic zinc oxide (ZnO) onto the surface of a garnet-type SE [ 153 ]. Generally, the garnet-type SE is widely used in SEs owing to its high energy density, electrochemical stability, high temperature stability, and safety [ 154 ]. Because of the ultrathin and conformal ZnO surface coating, molten Li reacts with ZnO and produces better contact with the surface of the garnet electrolyte by reducing the interfacial resistance ( Figure 14 a).…”
Section: Hybridized Use Of Electrolytes and Separators: Solid And mentioning
confidence: 99%
“…; ( b ) Ge-coated garnet electrolyte. Reprinted with permission from [ 154 ]. Copyright (2017) John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%
“…In contrast to Li-amalgam-LLTO cell, the pure Li-LLTO cell shows a poor contact between lithium metal and electrolyte even after cycling (Figure 3d,e). [40,41] XRD analysis reveals that Li-deficient alloy (LiHg 3 ) phase appearing in the interface can be transformed to Li-rich alloy (Li 3 Hg) phase ((JCPDF)-04-004-8747) after the first cycle (Figure 1l and Figure 3l), and SEM images show that the lithium amalgam interface between the metal anode and electrolyte undergoes a reversible phase transition from solid to liquid at room temperature during delithiation/lithiation cycling process (Figure 3g). Clearly, it can be observed that the liquid amalgam appears in the interface between lithium amalgam anode and electrolyte, when Liamalgam-LLTO cell is disassembled and broken down into two parts ( Figure S13, Supporting Information).…”
Section: Poor Cyclability and Safety Concerns Caused By The Uncontrolmentioning
confidence: 99%